THE IMPACT OF VIDEO-BASED DISCHARGE PLANNING ON THE FULFILLMENT OF DAILY ACTIVITIES AND JOINT RANGE OF MOTION EXERCISES ON FAMILY READINESS TO CARE FOR STROKE PATIENTS - Arofiati, Fitri; Hidayati, Novia Tri (Poltekkes Kemenkes Jakarta III, 2025)
Discharge planning is a systematic and methodical process. Family readiness is crucial and entails preparation in caregiving, educational provision, delineation of roles within the home, and the anticipation of obligations prior to the patient's departure. Video serves as a medium via which families can make informed decisions, enhance abilities, adjust to new circumstances, and refine cognitive patterns. Object. To assess the impact of video-based discharge planning on fulfilling daily demands and joint range of motion exercises on familial preparedness to care for stroke patients. Methods: This study employed a quantitative methodology with a pretest-posttest control group design. This study utilized a sample of 60 family members who will subsequently provide home care for stroke patients, employing a complete sampling technique. The subjects of this study were family members of stroke patients treated at PKU Muhammadiyah Gamping Hospital. The utilized instrument was a knowledge and skills questionnaire modified from prior research employing bivariate analysis methodologies. Results: The Mann Whitney U Test yielded a p-value of 0.001, which is less than α (0.05), indicating significant differences in preparedness outcomes between the intervention and control groups. In conclusion, video-based discharge planning for daily activity needs and joint range of motion exercises is deemed effective in enhancing family preparedness to care for stroke patients. p value (0.001) < α (0.05) means that there are differences in readiness results in the intervention group and control group. Video-based discharge planning on fulfilling daily activity needs and joint range of motion exercises is considered capable of increasing family readiness to care for stroke patients.